On the boundary value problems for ordinary differential equations with isolated singularity - Aldošina, Kristina; Rutkauskas, Stasys (Lietuvos matematikos rinkinys, 2005)
We consider some two-point boundary value problems for second order o.d.e. with strong singularity. The asymptotics of the solutions at the singular point are given. The existence and uniqueness of the solutions of those problems are prooved.